Reasons for Failure of Systemic-to-Pulmonary Artery Shunts in Neonates - Vitanova, Keti; Leopold, Cornelius; von Ohain, Jelena Pabst; Wolf, Cordula; Beran, Elisabeth; Lange, Rüdiger; Cleuziou, Julie (The Thoracic and Cardiovascular Surgeon, 2019)
Background Systemic-to-pulmonary artery shunt placement is an established palliative procedure for congenital heart disease. Although it is thought to be a simple operation, it is associated with significant morbidity and mortality.Methods Data for all neonates who underwent surgery for a systemic-to-pulmonary artery shunt between 2000 and 2016 were reviewed. The study endpoints were shunt failure and shunt-related mortality. Shunt failure was defined as a shunt dysfunction because of thrombosis or stenosis requiring intervention or reoperation; shunt mortality was defined as death because of a shunt dysfunction.Results A total of 305 shunts (central shunt, n = 135; Blalock–Taussig shunt, n = 170) were implanted in 280 patients. The median patients' age at the time of surgery was 9 days (1–31 days). The median shunt size was 3.5 mm (3–4 mm). Twenty-four patients (8%) were diagnosed with a shunt failure, with a median time of 7 days (0–438 days). Freedom from shunt failure at 1 year was 91.6% ± 2%. A shunt-related mortality was ascertained for 12 patients (4%). Freedom from shunt-related mortality at 1 year was 96% ± 1%. Perioperative platelet transfusion (p = 0.01), central shunt (p = 0.02), 3-mm shunt size (p = 0.02), and postoperative extra corporeal membrane oxygenation (ECMO) (p < 0.01) were identified as risk factors for shunt failure. Platelet transfusion (p = 0.04) and postoperative ECMO (p < 0.01) were further identified as risk factors for shunt mortality.Conclusion Based on these data, we recommend implanting a modified Blalock–Taussig shunt of at least 3.5 mm in neonates. Perioperative platelet transfusion and postoperative ECMO increase the risk of shunt failure.
Keywords: congenital heart disease; shunts; cardiac